The Corporation: A circular process of value creation - Goede, Miguel (Archives of Business Research, 2018)
Corporate governance is not new. It reached new heights in the 1980s when corporations became dominant in the era of neoliberalism. Corporate governance is about the way power is exercised over corporate entities. It covers the activities of the board and its relationships with the stakeholders or members, and with those managing the enterprise, as well as the external auditors, regulators and other legitimate stakeholders. Good corporate governance is an attempt to make corporations behave more ethically. The corporation is driven by short term profit. Good governance is governing according to the following principles: Honesty, Transparency, Accountability, Responsiveness, Independence, and Fairness. A more circular perspective on corporate governance might result in a more ethical corporation.